Retinal vasculature development in health and disease. (March 2018) - Selvam, Senthil; Kumar, Tejas; Fruttiger, Marcus
Abstract: Development of the retinal vasculature is based on highly coordinated signalling between different cell types of the retina, integrating internal metabolic requirements with external influences such as the supply of oxygen and nutrients. The developing mouse retinal vasculature is a useful model system to study these interactions because it is experimentally accessible for intra ocular injections and genetic manipulations, can be easily imaged and develops in a similar fashion to that of humans. Research using this model has provided insights about general principles of angiogenesis as well as pathologies that affect the developing retinal vasculature. In this review, we discuss recent advances in our understanding of the molecular and cellular mechanisms that govern the interactions between neurons, glial and vascular cells in the developing retina. This includes a review of mechanisms that shape the retinal vasculature, such as sprouting angiogenesis, vascular network remodelling and vessel maturation. We also explore how the disruption of these processes in mice can lead to pathology - such as oxygen induced retinopathy - and how this translates to human retinopathy of prematurity. Highlights: Retinal vasculature development is closely linked to retinal astrocytes. Neural-vascular interactions regulate retinal vasculature development. Sprouting angiogenesis is required for both primary and deeper plexus development. Vessel regression and vessel maturation remodel the primitive vascular network. Models of oxygen induced retinopathy allow for the study of pathological retinal vasculature development.